Influence of time to admission to a comprehensive stroke centre on the outcome of patients with intracerebral haemorrhage. (June 2020) - Prats-Sánchez, Luis; Guasch-Jiménez, Marina; Gich, Ignasi; Pascual-Goñi, Elba; Flores, Noelia; Camps-Renom, Pol; Guisado-Alonso, Daniel; Martínez-Domeño, Alejandro; Delgado-Mederos, Raquel; Rodríguez-Campello, Ana; Ois, Angel; Gómez-Gonzalez, Alejandra; et al.
Introduction: In patients with spontaneous intracerebral haemorrhage, it is uncertain if diagnostic and therapeutic measures are time-sensitive on their impact on the outcome. We sought to determine the influence of the time to admission to a comprehensive stroke centre on the outcome of patients with acute intracerebral haemorrhage. Patients and methods: We studied a prospective database of consecutive patients with intracerebral haemorrhage attended at two comprehensive stroke centres (2005–2017). We excluded patients with an unwitnessed time of onset of the intracerebral haemorrhage, or previous modified Rankin Scale >3 or in those in whom withdrawal of life-sustaining interventions were decided <24 h from admission. We recorded the time from the intracerebral haemorrhage onset to admission, demographic, clinical, radiological data, the functional outcome (favourable when modified Rankin Scale ≤3) and mortality at 90 days. We conducted a propensity score-matching analysis to evaluate functional outcome and mortality. Results: We included 487 patients (mean age 72.3 ± 13.9 years), and 53.2% were men. Compared to patients with an admission >110 min, patients who were admitted ≤110 min were significantly younger, and had higher National Institutes of Health Stroke Scale scores. Moreover, patients admitted ≤110 min were more likely to have basal ganglia intracerebral haemorrhage, and to show neurological deterioration. The propensity score groups were well matched. We did not find an association between time to admission and the favourable outcome (OR: 1.42 (95% CI: 0.93–2.16)) or mortality (OR: 0.64 (0.41–0.99)) at 90 days. Conclusions: Our results suggest that in patients with intracerebral haemorrhage and known symptom onset who are admitted to a comprehensive stroke centre, an early admission (≤110 min) does not influence the outcome at 90 days.